Hegemonic discourses on gender violence - Marugán Pintos, Begoña (Política y Sociedad, 2022)
The objective of this article is to describe the meaning given to violence against women in different periods from the concept crystallized in each era. Thus, a historical tour of the main agents and the hegemonic discourses of each moment will be made. Though these, it is observed that gender violence has gone from invisibility to visibility, from its visibility to an attempt to deny its existence. Although this position is a minority, it is hindering social progress.
Keywords: rape; domestic violence; gender violence; sexist violence; violence against women